Measuring Empowerment : Cross-Disciplinary Perspectives. - Narayan-Parker, Deepa (World Bank e-Library., 2005)
"Measuring Empowerment is an invaluable resource for planners, practitioners, evaluators, and students - indeed for all who are interested in approaches to poverty reduction that address issues of inequitable power relations."--Jacket.